Circular RNA circABCC4 as the ceRNA of miR‐1182 facilitates prostate cancer progression by promoting FOXP4 expression. Issue 9 (3rd July 2019) - Huang, Changkun; Deng, Huanghao; Wang, Yinhuai; Jiang, Hongyi; Xu, Ran; Zhu, Xuan; Huang, Zhichao; Zhao, Xiaokun
Abstract: In recent years, circular RNAs (circRNAs) have been identified to be essential regulators of various human cancers. However, knowledge of the functions of circRNAs in prostate cancer remains very limited. The correlation between circABCC4 and human cancer is largely unknown. This study aims to investigate the biological functions of circABCC4 in prostate cancer progression and illustrate the underlying mechanism. We found that circABCC4 was remarkably up‐regulated in prostate cancer tissues and cell lines and promoted FOXP4 expression by sponging miR‐1182 in prostate cancer cells. CircABCC4 knockdown markedly suppressed prostate cancer cell proliferation, cell‐cycle progression, migration and invasion in vitro. Furthermore, silencing of the circRNA also delayed tumor growth in vivo. Taken together, our findings indicated that circABCC4 facilitates the malignant behaviour of prostate cancer by promoting FOXP4 expression through sponging of miR‐1182. The circABCC4–miR‐1182‐FOXP4 regulatory loop may be a promising therapeutic target for prostate cancer intervention.